Astroglia as a cellular target for neuroprotection and treatment of neuro‐psychiatric disorders. Issue 8 (16th March 2017) - Liu, Beihui; Teschemacher, Anja G.; Kasparov, Sergey
Abstract: Astrocytes are key homeostatic cells of the central nervous system. They cooperate with neurons at several levels, including ion and water homeostasis, chemical signal transmission, blood flow regulation, immune and oxidative stress defense, supply of metabolites and neurogenesis. Astroglia is also important for viability and maturation of stem‐cell derived neurons. Neurons critically depend on intrinsic protective and supportive properties of astrocytes. Conversely, all forms of pathogenic stimuli which disturb astrocytic functions compromise neuronal functionality and viability. Support of neuroprotective functions of astrocytes is thus an important strategy for enhancing neuronal survival and improving outcomes in disease states. In this review, we first briefly examine how astrocytic dysfunction contributes to major neurological disorders, which are traditionally associated with malfunctioning of processes residing in neurons. Possible molecular entities within astrocytes that could underpin the cause, initiation and/or progression of various disorders are outlined. In the second section, we explore opportunities enhancing neuroprotective function of astroglia. We consider targeting astrocyte‐specific molecular pathways which are involved in neuroprotection or could be expected to have a therapeutic value. Examples of those are oxidative stress defense mechanisms, glutamate uptake, purinergic signaling, water and ion homeostasis, connexin gap junctions, neurotrophic factors and the Nrf2‐ARE pathway. We propose that enhancing the neuroprotective capacity of astrocytes is a viable strategy for improving brain resilience and developing new therapeutic approaches. Main Points: Many processes localized in astroglia are potentially neuroprotective In this review we examine how astroglial dysfunction contributes to neurodegeneration and major neurological disorders and explore potential drug targets localized to astrocytes.